THE ROLE OF THE US SUPREME COURT IN THE LEGAL SYSTEM (Journal of actual problems of jurisprudence, 2019)
The purpose of the article on the topic of judicial law-making in the USA, which attempts to invade the educational process and intensify the study of the History of State and Law of Foreign Countries, is devoted to the US Supreme Court – the founder of constitutional justice and one of the pillars in the system of separation of powers. This is a unique judicial institution with an exceptional degree of influence, about which America’s famous political writer Alexis do Tocqueville stated that «never before have any people had such a powerful judicial authority». For the reader, the phenomenon of the US Supreme Court is interesting in several ways. First, from the point of view of the evolution of American law and the judicial system in all its dynamics and contradictions. Secondly, in terms of implementation of judicial activity, complex thought processes of finding the right precedents and arguments in a particular case, reaching (if possible) a compromise between judges and colleagues. Judge activity should be interpreted not only as based on law, but also subject to ideological and political influences. Objective: to identify the features of the law-making activities of the US Supreme Court, since judicial law-making in science remains an unsolved problem. Finally, it is very important to look at the US Supreme Court in the eyes of American history as an institution that has the potential to come into conflict with both the legislature and the executive branch. On the other hand, it is important to understand the logic of filling vacancies in the Supreme Court by the executive branch. In the course of continuing in this country, the search for the causes of negative political and legal phenomena, attention is drawn to the interpretation of the federal Constitution by the US Supreme Court, in general, to the activities of this court, which performs the law-making function, is alien to it and is constitutionally unfounded. However, many issues remain insufficiently studied, among them the role of the US Supreme Court in constitutional lawmaking, the very phenomenon of judicial lawmaking.Key words: lawmaking, jurisdiction, Supreme Court, USA, legislature.